2002
DOI: 10.1097/00000539-200202000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Anesthesia for Cardiac Surgery: The Effects on Tracheal Intubation Time and Length of Hospital Stay

Abstract: We found that epidural analgesia was more effective than IV morphine for cardiac surgery. Epidural anesthesia also allowed earlier weaning from mechanical ventilation, but it did not affect hospital discharge time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 17 publications
0
48
1
4
Order By: Relevance
“…However, the groups were similar with respect to this outcome, by the third postoperative day. These results differ from those of Priestley et al 5 who were unable to show a difference, on chest radiographs, between the groups of patients with and without epidurals. it is plausible that the atelectasis scores were initially lower in the epidural group, because these patients had significantly less pain, and were, therefore, more compliant with deep breathing and coughing exercises.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the groups were similar with respect to this outcome, by the third postoperative day. These results differ from those of Priestley et al 5 who were unable to show a difference, on chest radiographs, between the groups of patients with and without epidurals. it is plausible that the atelectasis scores were initially lower in the epidural group, because these patients had significantly less pain, and were, therefore, more compliant with deep breathing and coughing exercises.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there have been conflicting reports regarding the effects of TEA on postoperative pulmonary function and atelectasis. [3][4][5][6] A recent meta-analysis by Liu et al 12 with a combined total of 1,178 patients, found that TEA decreased the incidence of pulmonary complications. in the present study, TEA was associated with a significant improvement in pulmonary function during the first two postoperative days, using FEV 1 as a surrogate for pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thoracic epidural analgesia (TEA) is advantageous as adjunctive anesthesia and analgesia to fast-track patients after cardiac surgery [1][2][3] with superior pain management, [4][5][6][7][8][9] reduced opioid requirements, improved pulmonary function, 10,11 and myocardial protection. 12,13 Maintenance of body temperature is an important factor in achieving immediate extubation after OPCAB as shown by a recent retrospective study of ten patients, who were extubated in the operating theatre after OPCAB.…”
Section: Résultats : On a Pu Extuber 95 Patients Pendant Les 25 Premimentioning
confidence: 99%